Sistem Informasi Perhitungan Upah Lembur Karyawan (SIPULEN) Berbasis Web - Wahidah, Rizka Nurul; Mustika, Wida Prima; Drevianto, Rian; Septiyo, Panji (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Information Technology (IT) develops to support all activities within the company. One of these information technologies is an information system, an information system for calculating employee overtime wages at PT. Metal Castindo Industritama. In the process of applying for overtime, current employees take a long time and a long process. One of them is by filling out an overtime application form or commonly called an Overtime Work Order (SPKL) for each overtime employee, considering that the number of employees working overtime at the same time is not small. One of the problems is errors that often occur when calculating the total overtime pay for employees. To overcome this challenge, we need a system that simplifies the process of reporting employee overtime data and calculating employee overtime pay quickly and accurately. This research begins with an ongoing system analysis, obtained through direct interviews with stakeholders and field observations. The software development model uses the waterfall model, and the design method uses UML to describe the system design. The purpose of this system is to create a simple and accurate system for submitting employee overtime hours and calculating employee overtime wages so that there is no need for a long procedure. In addition, the performance of superiors is more effective and efficient because of the computer-managed website-based information system. The data is stored in the database system, so the whole process does not require a lot of paper